Promotion Strategy in Supporting Business Development and Competitiveness of Private Higher Education Institutions - Nitaleari, Ni Wayan; Kusuma, Gusti Putu Eka; Gorda, A.A.N. Eddy Supriyadinata; Nurkariani, Ni Luh (Yayasan Riset dan Pengembangan Intelektual, 2025)
The Covid-19 pandemic has resulted in teaching and learning to be carried out from home. Competition between private schools has increased so that the need for the right strategy to promote in the new normal era, one of which is through media sosial, to be able to continue to promote without violating health protocols. This study aims to determine the role of media sosial marketing in the promotion of private schools in Bali in the new normal era. This study took the object of the Dynata School. The strategy in this study was formulated by using a SWOT analysis and analyzing the media sosial platforms used by the school (Facebook, Instagram and Youtube). The data collected is in the form of in-depth interviews with a qualitative research design. Data analysis processing techniques used are data reduction, data presentation, comparative analysis, and drawing conclusions. The results of this study are the school's marketing management strategy through digital marketing at the Dynata School Denpasar in the new normal period using the Threat Strength (ST) strategy. The Dynata School must be able to use and improve its strengths to overcome the existing threats. The implementation of the ST Strategy is carried out by highlighting the strengths of the Dynata School in implementing school promotions through the Media sosial Marketing platform, namely Instagram, Facebook and the school's Youtube. Quality improvement carried out thoroughly from the results of the analysis will have a positive impact on parents' decisions to choose Dynata School as the right educational institution for students.